Pengaruh Tekanan, Kompleksitas Tugas Dan Pengalaman Auditor Terhadap Audit Judgement - Hajering, Hajering; Su’un, Muhammad; Muslim, Muslim (Jurnal Ilmiah Akuntansi Peradaban, 2023)
The purpose of this research is to examine and analyze the influence of compliance pressure, task complexity, and auditor work experience on audit judgement. The population in this study comprises all auditors working at the South Sulawesi Representative Office of the Supreme Audit Agency (BPK) in Makassar, totaling 95 individuals. The data source used is primary data, collected directly from respondents using a questionnaire instrument. Data analysis methods to be employed include descriptive statistical analysis, validity testing, reliability testing, classic assumption testing, as well as hypothesis testing through multiple linear regression analysis, coefficient of determination test, t-test, and F-test. The research findings indicate that the variables of compliance pressure, task complexity, and work experience have a positive and significant influence on audit judgement. Keyword: Compliance Pressure, Task Complexity, Work Experience